ปัจจัยที่ก่อให้เกิดความขัดแย้งในการปฏิบัติงานระหว่างที่ปรึกษาโครงการและผู้รับเหมาก่อสร้าง - สุรชัย ทาสุวรรณอินทร์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Construction projects consist of a lot of parties, whose roles and responsibilities are different depending on the nature of each party. Conflicts between the consultants and the contractors may adversely affect the success of the project. This research aims to investigate the causes, the frequency and the severity of the conflicts between consultants and contractors, and to propose ways to resolve the disputes. The research instrument is a set of questionnaires asking about the frequency of the conflicts, and the effects of the conflicts on the construction, with three major factors, namely personnel factors, duty and responsibility factors, and document factors. In addition, questions regarding the solutions to the conflicts were asked. The sample group consisted of thirty consultants and thirty contractors. The research found that expediting the work of the contractors was the most frequent cause of conflicts in the construction. Also, the number of construction workers was not sufficient for the total volume of work, causing the conflicts with the highest level of impact severity. This was also a cause of the most significant conflict. The best solutions to the conflicts between the consultants and the contractors were compromising, followed by cooperating. Comparing the views on how to solve the conflicts, it was found that the opinions of the consultants and the contractors were not different.